Effect of Music Therapy on Anxiety Levels in Circumcised Children in The Senduro Health Center Area - Bagus Eka Windarta; Nafolion Nurahmat; Yuliah Rahmawati H (KHD Production, 2024)
Circumcision is a minor surgical procedure that often causes fear and pain in children, making them anxious. If this anxiety is not addressed, it can cause the child to be uncooperative and interfere with the circumcision process. Therefore, both distraction and relaxation therapy are needed to overcome anxiety, one of which is religious music therapy. Religious music therapy is a therapy that involves interpersonal processes using music for physical, emotional, mental, social, aesthetic, and spiritual aspects of therapy to help patients improve or maintain their health. This type of research is a pre-experimental study using a one group pretest-posttest approach. The sampling technique used is accidental sampling, with 30 children as a sample who will undergo circumcision according to the inclusion criteria of the study. Data was collected using the State-Trait Anxiety Inventory (STAI) questionnaire. The results of this study indicate that there is a significant effect between the provision of religious music therapy on reducing anxiety in circumcised children, with the results of the Wilcoxon statistical test obtaining a p-value of 0.000 (p <0.05). Physiologically, music therapy will mutate the brain so it can release the analysis process of the song being heard, affect the pituitary to release the hormone beta-endorphin, reduce cortisol or anxiety-triggering hormones so that it can make someone calmer and provide a sense of security that is very helpful in reducing anxiety levels. When listening to music, the stimulus activates the hormone endorphin to help increase relaxation in a person's body.